INTRODUCING THEORY LINKING GENESIS OF HAIR SHAFT BIPOLARITY WITH ARRECTOR PILI MUSCLE PROXIMAL ATTACHMENT - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2021)
Previous publications described the presence of bipolarity or (+−) electrical charges in the human hair shaft, this due to an apparent segmental electromagnetic radiation Gap demonstrated by a total absence of precipitated Potassium Ferricyanide crystals. In this manuscript additional data is presented elucidating the genesis of said absence. The in vitro experiments showing a correlation between a segmental absence of longitudinal terminal palisades nervous endings prevalent in the rest of the outer membrane in the hair follicle anatomy. Due to their intrinsic metabolism, nerve cells do emit electromagnetic radiation; their absence not allowing for the positive (+) charge of zero precipitated Potassium Ferricyanide crystals to reach one side of the shaft. In addition it was concluded that there are two types of human hair images. The first by optical microscopy, the second a functional one obtained from electromagnetic radiation precipitating Ferricyanide crystals.